A natureza das inovações em agroindústrias de arroz do Rio Grande do Sul - Paraginski, Ana Laura (2012)
The innovations in organizations have as one of its main consequences development value in processes in certain activities so that the same can increase their level of competitiveness. Between other aspects, the innovations may be motivated by demands from the consumer (demandpull), but also may be motivated by the needs and opportunities identified by the various departments of a business or by managers (technology-push). This work aims to investigate the nature of innovations in rice s agroindustries of small, medium and large, using the Value Chain and model of Innovation s Steps. The methodology central qualitative method was chosen by analyzing multiple cases. Were elected nine rices agroindustries and addressed through a semi-structure interview. The results indicate that the companies of different sizes have priorities for investment in innovations of different natures. In terms of radical innovations, while small businesses are concerned with inbound logistics and infrastructure, the midsize prioritize investments in the processing of the product and the large aim innovations in marketing, sales and purchasing department. This search also identified that the innovations of a radical nature are located primarily in the primary activities of the value chain. As for innovations of incremental nature, they are in several departments, but mainly in support activities of value chain. It was concluded that the innovations made in the studied sector have their origin, primarily, in the demands from the market and institutional environment are, therefore, demand-pull type.